A gestão previdenciária e a sua potencialidade lesiva à esfera moral do beneficiário da Previdência Social - Brum, Gustavo (2016)
In this work, attention is directed to the compatibility of the civil liability structure in situations of potential injury to the moral sphere of those insured under social security. The nature of social risks covered up by the state welfare structure was considered during the characterization of the social security authority s duty to compensate the insured. The field of analysis was restricted to benefits that were rejected by public administration and afterwards reviewed by the judiciary, through the verification of the illegality of such acts, with the aim of providing the benefit to the insured in court. Compensatory damages are not characterized by the mere improper rejection of benefits, because they are not in re ipsa compensatory damages. On the other hand, it was criticized the understanding which exempts from responsibility the public entity, under the argument of regular exercise of law, when the administrative act is emanated from within a certain margin of interpretative reasonableness of the social security rule. Permeating the criteria and assumptions of civil liability by public administration, it was concluded that the duty to reimburse compensatory damages regarding social security requires the attendance of a normative cause. Grounded on that theory, considering that welfare activity decreases the risks to which the insured is exposed, the losses are only attributable to social security when its operations frustrate the legal expectations of the insured. To characterize this frustration, it is required that public administration misuses the interpretation/application of social security rules. In turn, the parameters of public administration s operation can be objectively evaluated considering the situation of the insured in view of their legal position within the social security system